Feasibility Study for D-Lactic Acid Production from Thai Rice by Leuconostoc pseudomesenteroides TC49 and D-Lactic Acid Purification - Tasneem Chemama (Faculty of Science, Chiang Mai University, 2020)
Chiang Mai Journal of Science